SUBJECT OLYMPIADS AS AN INDICATOR OF THE QUALITY OF EDUCATION IN THE ARMENIAN SCHOOL OF IRAN (2000-2008) (EDUCATION IN THE 21ST CENTURY, 2025)
The subject Olympiads, organized by the Ministry of Education of the Islamic Republic of Iran and the relevant provincial and metropolitan institutions under its jurisdiction, are aimed at identifying students with gifted, talented and creative abilities, developing interest in academic subjects and promoting the acquisition of sustainable knowledge. They also provide an opportunity to make sure that real, exemplary teenagers study in Iranian, including Armenian schools.For Armenians, this is seen as a way to entrust the youth with the leadership of their own community structures. In this regard, the undeniable role of teachers deserves recognition, thanks to whose tireless efforts students reach new heights.In the Iranian educational environment, where Islamic religious ideology prevails, it is not easy to develop one's own traditions of the Armenian school. That’s why an attempt is being made to synthesize Armenian educational components with Iranian ones.The participation of talented Armenian students and their leading positions in school subject Olympiads is important for the community's activities. Thus, Armenians emphasize their presence in the Iranian environment in general and in the educational sphere in particular. It is obvious that, in addition to the inspiring effect, victories at subject Olympiads give a new boost to the younger generation, emphasize the real potential of the community, and also, most importantly, reveal intellectual abilities.Thus, when compared with the educational level of the Iranian population as a whole, including minorities, in the 2000s, the number of applicants in technical and natural sciences in the Armenian community and the results achieved by talented students in school subject Olympiads indicate a high quality of education.
Keywords: Subject Olympiads; Iranian Armenian school; student; university; quality of education; talented students; exam; competition